HORMONAL THERAPY IN HIGH-GRADE SEROUS OVARIAN CARCINOMA: A REVIEW OF CURRENT EVIDENCE - Agnieszka Zaręba; Dawid Juszkiewicz; Krzysztof Kiełczewski; Barbara Fetner; Magdalena Dłużewska; Zuzanna Gebert; Ivanna Ilkiv; Agata Kucharska; Konrad Adler; Patrycja Stanowska (International Journal of Innovative Technologies in Social Science, 2026)
Ovarian cancer remains one of the leading causes of cancer-related mortality among women worldwide. The most common histological subtype is high-grade serous ovarian carcinoma (HGSOC), which accounts for approximately 70-80% of epithelial cases and is characterized by profound genomic instability, nearly universal TP53 mutations, and a high propensity for recurrence. While the standard of care - comprising maximal cytoreductive surgery, platinum-based chemotherapy, and maintenance with poly (ADP-ribose) polymerase PARP inhibitors or anti-angiogenic agents- has improved outcomes, long-term prognosis for advanced disease remains poor. Hormonal therapy (HT) has emerged as a clinically relevant treatment option for selected patients with recurrent ovarian cancer, particularly in oestrogen receptor (ER)- positive tumours. Agents such as Tamoxifen and aromatase inhibitors (AIs), including Letrozole, Anastrozole, and Exemestane, demonstrate reproducible clinical benefit rates of 25-45%, primarily through disease stabilisation. Recent real-world cohort data (2025) and ongoing prospective trials- notably the phase III ENGOT-ov54/Swiss-GO-2/MATAO trial (NCT04111978) - represent critical steps towards establishing evidence-based endocrine therapy in HGSOC. This review evaluates the biological rationale for targeting the ER and progesterone receptor (PR) pathways, critically appraises current and emerging clinical evidence, discusses combination strategies with CDK4/6 inhibitors, PI3K/mTOR inhibitors, and PARP inhibitors, and highlights the unmet need for biomarker-driven patient selection.